2002
DOI: 10.1159/000064926
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Alzheimer’s Disease Might Be Associated with Apolipoprotein E ε4 Allele Frequency in Women but Not in Men

Abstract: The association between depression and apolipoprotein E (apoE) was investigated in 137 out-patients with Alzheimer’s disease. An ICD-10 diagnosis of depression was found in 21.1% of all patients. There was a good correlation between clinicians’ diagnoses and blinded rating by the Montgomery-Åsberg Depression Rating Scale (r = 0.70). In male patients, apoE 3/3 was detected in 34.1%, 3/4 in 38.6%, 4/4 in 13.6%, 2/4 in 6.8% and 2/3 in 6.8% of cases. In female patients, apoE 3/3 was detected in 35.5%, 3/4 in 45.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…These findings are consistent with those of Müller-Thomsen (2002) who indicated that the APOE ε4 genotype may be more highly associated with depression in AD for women but not men. Our finding is also supported by a study showing an increased rate of the APOE ε4 genotype in late-onset depressed women with AD relative to men (Steffens et al, 1997) as well as a finding that family history of depression may be a risk factor for depression in AD, but only in women (Lyketsos, Tune, Pearlson, Steele, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of Müller-Thomsen (2002) who indicated that the APOE ε4 genotype may be more highly associated with depression in AD for women but not men. Our finding is also supported by a study showing an increased rate of the APOE ε4 genotype in late-onset depressed women with AD relative to men (Steffens et al, 1997) as well as a finding that family history of depression may be a risk factor for depression in AD, but only in women (Lyketsos, Tune, Pearlson, Steele, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…However, among ApoE ε4 noncarriers, the MCI subjects had lower premorbid and current neuroticism and higher premorbid and current extraversion scores compared to the control subjects, whereas the MCI patients and the control subjects who were ApoE ε4 carriers obtained similar scores. To our knowledge, this is the first study reporting on ApoE status in relation to personality traits in MCI, although there are a number of investigations into BPS as state markers in AD showing contradictory findings as to their association with the ApoE ε4 genotype [18,19,20,21,22,23,24,25]. Our results may be a chance finding given the preliminary nature of this study.…”
Section: Discussionmentioning
confidence: 58%
“…Apolipoprotein E ε4 allele (ApoE ε4) and tau protein were associated with MCI conversion to AD [15,16,17]. Moreover, BPS as state markers in AD have been found to be associated with ApoE ε4 and less with ApoE ε3 genotypes [18,19,20,21,22,23], although some studies contradict such findings [24,25]. We have found no studies reporting on ApoE status in relation to BPS and personality traits in MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of positive associations between depression and the apolipoprotein E epsilon 4 allele has suggested that men may have resilience against this potential risk factor (Müller-Thomsen et al, 2002) which may include pathways such as capacity for intensive aerobic activity (Russo-Neustadt, Ha, Ramirez, & Kesslak, 2001;Southwick, Vythilingam, & Charney, 2005). Other studies have suggested that the majority of people who have genetic variants associated with higher risk of psychopathology may obtain or develop bio-and psycho-social resilience (Freedman, 2008).…”
Section: Some Potential Multi-level Mechanisms Conferring Resiliencementioning
confidence: 99%